(untitled) (International Journal of Engineering and Computer Science, 2015)
— A real time operating system (RTOS) is a specified time constraint in the real time application. A process of RTOS using Open Mp, multiple tasks are concurrently running on the system. A large number of embedded applications required multiple concurrent real-time tasks. In a concurrent real-time tasks, the task scheduling and memory allocation are done on Uni-processor. These two functions are performed separately; tasks are scheduled first and then partitioned among the processors. So, it requires an additional memory and also the waste of time period for every task. Instead of cache memory, using SPM (Scratch Pad Memory) the execution time of embedded applications will be accurately prefixed. (RR) Round Robin Scheduling is used to complete a task. Every task had a scratch pad number for the allocation. Depending upon the Round Robin scheduling and Scratch pad number the task should be completed within a given time period